Study on the effect of the temperature in acoustic emission sensor by the pencil lead break test - Lopes, Barbara Guedes [UNESP]; Alexandre, Felipe Aparecido [UNESP]; Lopes, Wenderson Nascimento [UNESP]; Aguiar, Paulo Roberto De [UNESP]; Bianchi, Eduardo Carlos [UNESP]; Viera, Martin Antonio Aulestia [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2019)
The Pencil Lead Break (PLB) method is used to reproduce an artificial source of acoustic emission. This method consists of breaking a pencil lead which has its size and thickness determined carefully in a certain angle in a surface. This break releases energy in the form of elastic stress waves which propagate through the structure and are captured and converted into electrical signals by a sensor fixed to the workpiece surface. The PLB method is very efficient in the characterization of acoustic emission sensors. In this paper, the effect of temperature variation in the acoustic emission sensor response was investigated through the PLB method and digital signal processing. The results show that in the frequency response not only the temperature but also the analyzed frequency bands are factors that influence the amplitude of the signals. When comparing signals at different temperatures, the magnitude difference in amplitude increases proportionally to the temperature.
Keywords: Acoustic Emission; Pencil Lead Break; System Monitoring; Temperature